'MHC-I-opathy'-unified concept for spondyloarthritis and Behcet disease - DİRESKENELİ, RAFİ HANER (NATURE PUBLISHING GROUP, 2015)
The spondyloarthropathies comprise ankylosing spondylitis (AS), reactive arthritis, psoriatic arthritis (PsA) and arthritis associated with inflammatory bowel disease. In this Perspectives article, we describe how Behvet disease and several clinically distinct spondyloarthropathies-all associated with MHC class I (MHC-I) alleles such as HLA-B*51, HLA-C*0602 and HLA-B*27 and epistatic ERAP-1 interactions-have a shared immunopathogenetic basis. As a unifying concept, we propose that barrier dysfunction in environmentally exposed organs such as the skin, and aberrant innate immune reactions at sites of mechanical stress, can often trigger secondary adaptive immune CD8+ T-cell responses with prominent neutrophilic inflammation that culminate in exacerbation and recurrence of these diseases. Of note, these 'MHC-I-opathies' show a differential immunopathology, probably reflecting antigenic differences within target tissues: HLA-B*51 is linked to ocular and mucocutaneous disease but not gut involvement, and HLA-C*0602 is linked to type I psoriasis but not scalp or nail disease.
Keywords: GENOME-WIDE ASSOCIATION; RETICULUM AMINOPEPTIDASE 1; HISTOCOMPATIBILITY COMPLEX ASSOCIATIONS; INFLAMMATORY-BOWEL-DISEASE; CYTOTOXIC T-LYMPHOCYTES; ANKYLOSING-SPONDYLITIS; PSORIATIC-ARTHRITIS; SUSCEPTIBILITY LOCI; ANTERIOR UVEITIS; BIOMECHANICAL FACTORS